2015
DOI: 10.1002/rob.21556
|View full text |Cite
|
Sign up to set email alerts
|

Actuator Control for the NASA‐JSC Valkyrie Humanoid Robot: A Decoupled Dynamics Approach for Torque Control of Series Elastic Robots

Abstract: This paper discusses the actuator-level control of Valkyrie, a new humanoid robot designed by NASA's Johnson Space Center in collaboration with several external partners. Several topics pertaining to Valkyrie's series elastic actuators are presented including control architecture, controller design, and implementation in hardware. A decentralized approach is taken in controlling Valkyrie's many series elastic degrees of freedom. By conceptually decoupling actuator dynamics from robot limb dynamics, the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
124
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(164 citation statements)
references
References 35 publications
0
124
2
Order By: Relevance
“…In addition, the spring can be used to measure the joint torque. However, SEA makes the robot control more complex as the actuator dynamics needs to be taken into account [11].…”
Section: A Availability Of Recent Humanoid Robot Technologiesmentioning
confidence: 99%
“…In addition, the spring can be used to measure the joint torque. However, SEA makes the robot control more complex as the actuator dynamics needs to be taken into account [11].…”
Section: A Availability Of Recent Humanoid Robot Technologiesmentioning
confidence: 99%
“…Despite these difficulties, SEA has been applied to robotic applications in various fields to take advantage of the high fidelity force control of SEA [3][4][5][6][7][8][9][10][11][12]. Lots of applications of SEA for quadruped robots, biped robot, dual arm robots and wearable robots, have demonstrated that SEA is the promising actuator system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have been widely used in many advanced robot applications, e.g., industrial robots of the Rethink robotics, the Valkyrie and COMAN humanoid robots, and the RoboKnee and LOPES exoskeletons [17][18][19][20][21]. The motion control problem of SEAs is more complicated than that of conventional actuators due to their fourth order dynamic model.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the robustness and performance of the real force control implementations, Disturbance Observer (DOb) was first applied to an SEA by Kong et al [24]. The robust force controller was also similarly applied to the University of Texas's SEA (UT-SEA) and Valkyrie in [18,25]. In these applications, DOb is designed for the velocity feed-back loop which is used to improve the stability of SEAs in [15,22].…”
Section: Introductionmentioning
confidence: 99%